Overexpression of Mitochondrial Ferritin Enhances Blood–Brain Barrier Integrity Following Ischemic Stroke in Mice by Maintaining Iron Homeostasis in Endothelial Cells - Peina Wang; Qianqian Ren; Mengtong Shi; Yuanyuan Liu; Huiyuan Bai; Yan-Zhong Chang (Antioxidants, 2022)
Blood–brain barrier (BBB) breakdown, a characteristic feature of ischemic stroke, contributes to poor patient outcomes. Brain microvascular endothelial cells (BMVECs) are a key component of the BBB and dysfunction or death of these cells following cerebral ischemia reperfusion (I/R) injury can disrupt the BBB, leading to leukocyte infiltration, brain edema and intracerebral hemorrhage. We previously demonstrated that mitochondrial ferritin (FtMt) can alleviate I/R-induced neuronal ferroptosis by inhibiting inflammation-regulated iron deposition. However, whether FtMt is involved in BBB disruption during cerebral I/R is still unknown. In the present study, we found that FtMt expression in BMVECs is upregulated after I/R and overexpression of FtMt attenuates I/R-induced BBB disruption. Mechanistically, we found that FtMt prevents tight junction loss and apoptosis by inhibiting iron dysregulation and reactive oxygen species (ROS) accumulation in I/R-treated BMVECs. Chelating excess iron with deferoxamine alleviates apoptosis in the brain endothelial cell line bEnd.3 under oxygen glucose deprivation followed by reoxygenation (OGD/R) insult. In summary, our data identify a previously unexplored effect for FtMt in the BBB and provide evidence that iron-mediated oxidative stress in BMVECs is an early cause of BMVECs damage and BBB breakdown in ischemic stroke.